Psychological stimulation as a performance technique in monodrama performances - Prof. Dr. Nashat mubarak sliwa; Abdaleazim Hamad Mohammed (Genius Journals, 2022)
The research aims to identify the impact of the strategy of your questions and my answers on the achievement of the students of the College of Education in the course of teaching methods of Arabic language and thinking outside the box for them. Her students are (37) male and female students, and in a random drawing method, the researcher chose (third stage students / Department of Arabic Language / College of Basic Education / University of Babylon). (Academic achievement, thinking outside the box), as the researcher chose the experimental design to control the research variables. out of the box), and after making the equivalence between the two research groups, the researcher prepared the requirements of the application of plans, objectives and tests for the two research groups, and after completing the application of the experiment. b The researcher applied her research tools to the two research groups, to obtain the final results by treating those data statistically by means of a t-test for two independent samples.
Keywords: Your questions and answers strategy; academic achievement; thinking outside the box; teaching methods